Composition, abundance, and distribution of major zooplankton taxa in the upwelling region off the coast of Northern Zamboanga peninsula - Valderama, Mary Christine C.
Zooplankton composition, abundance, and distribution of three depth strata (0-65m, 65-135 m, 135-200m) of five stations (stations 7-11) in the upwelling region off the coast of the Zamboanga Peninsula are presented based on the analysis of the samples collected using a double trip close-open-close system, standard NORPAC 200 µm mesh net during an oceanographic cruise form March 4-9, 2014 on board the M/V DA-BFAR. Zooplankton density ranged form 1073.64 - 2491.25 ind.?m-3 with an overall mean density of 1590 ind.?m-3. Maximum and minimum densities of zooplankton recorded were 2491.25 ind.?m-3 in station 8 and 1073.63 ind.?m-3 in station 10, respectively. 33 taxonomic groups were identified form the samples. In order of mean density, the top nine with densities greater than 1 ind.?m-3 include: calanoids, cyclopoids, poecilostomatoids, appendicularians, copepod nauplii, chaetognaths, gastropods, mysids, and cladocerans. Copepods dominated the zooplankton in the area. Calanoids were the most abundant group and constituted 66.17% (1051.91 ind.?m-3), followed by the cyclopoids that were 17.22% (273.69 ind.?m-3), and the poecilostomatoids with 3.29% (52.29 ind.?m-3). Zooplanktons were more concentrated in the middle stations which were located offshore. Highest densities were found on the surface layer and a significant difference was shown in the mean zooplankton densities between depth strata (F(3,10)= 4.521, p=0.030).